2022
DOI: 10.3389/fimmu.2022.879754
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Crosstalk of Immune Cells in Pathogenesis of Chronic Spontaneous Urticaria

Abstract: Chronic spontaneous urticaria (CSU) is defined as recurrent episodes of spontaneous wheal development and/or angioedema for more than six weeks and at least twice a week. The core link in the pathogenesis of CSU is the activation of mast cells, T cells, eosinophils, and other immune cells infiltrating around the small venules of the lesion. Increased vascular permeability, vasodilatation, and recruitment of inflammatory cells directly depend on mast cell mediators’ release. Complex regulatory systems tightly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 217 publications
0
49
0
Order By: Relevance
“…Apart from that, classical monocytes may play a central role in severe COVID-19 ( 38 ). In addition, the researchers found that in CU, Toll-like receptors agonists could induce the expression of TFs of monocytes, and the TFs increased vascular permeability in a histamine-independent way, leading to the formation of a wheal ( 39 ). In some way, these results may hint that the shared DEGs could play a role in the immunoregulation of CU and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, classical monocytes may play a central role in severe COVID-19 ( 38 ). In addition, the researchers found that in CU, Toll-like receptors agonists could induce the expression of TFs of monocytes, and the TFs increased vascular permeability in a histamine-independent way, leading to the formation of a wheal ( 39 ). In some way, these results may hint that the shared DEGs could play a role in the immunoregulation of CU and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these principles is complex, and according to current knowledge, aside from humoral (autoantibodies), it also involves cellular responses (auto-reactive T cells) and the dysfunction of adaptive cellular immunity [ 19 , 20 ]. According to current literature data, crucial pathogenetic factors/events for CSU are the activation of mast cells, basophils, T cells, and eosinophils, as well as increased vascular permeability and vasodilation, activation of coagulation pathways and autoimmunity processes, and finally, the release of mast cell mediators [ 21 ]. Thus, CSU involves the participation of both innate immunity (mast cells, basophils, neutrophils, eosinophils, monocytes, macrophages, natural killer [NK] cells, innate lymphocytes [ILC], complement factors) and adaptive immunity (Th1 and, Th2 cells, Th9 cells, Th17 cells, regulatory T cells [Treg cells], B cells, antibodies), wherein mast cells link innate and adaptive immunity.…”
Section: Immunopathogenesis Of Chronic Urticarial and Immune Changes ...mentioning
confidence: 99%
“…Thus, CSU involves the participation of both innate immunity (mast cells, basophils, neutrophils, eosinophils, monocytes, macrophages, natural killer [NK] cells, innate lymphocytes [ILC], complement factors) and adaptive immunity (Th1 and, Th2 cells, Th9 cells, Th17 cells, regulatory T cells [Treg cells], B cells, antibodies), wherein mast cells link innate and adaptive immunity. Mast cells have various roles: they induce/modulate T-cell activation and polarization; stimulate B cells to produce IgE (through IL-4 and IL-13); produce mediators (e.g., TNFα), which act on vascular endothelial cells’ up-regulation and adhesion molecules‘ expressions, which promote the recruitment of T cells; allergen-specific Th2 cells stimulate B cell production of IgE, which stimulates/activates mast cells and basophils [ 21 ]. In the skin tissue of urticarial CSU lesions, mast cells predominate, and there are increased numbers of basophils, eosinophils, macrophages, neutrophils and T cells, while there are decreased numbers of Th17 cells.…”
Section: Immunopathogenesis Of Chronic Urticarial and Immune Changes ...mentioning
confidence: 99%
See 2 more Smart Citations